Clinical and metabolic profile and its relationship with insulin resistance among school children - Jéssica Denise Vieira Leal; Thaís Norberta Bezerra de Moura; Vanessa Natali de Carvalho; Ana Roberta Vilarouca da Silva; Artemízia Francisca de Sousa; Luisa Helena de Oliveira Lima (Rev Rene)
Objective: to investigate the clinical and metabolic profile and its relationship with insulin resistance among school children. Methods: a Cross-sectional study of 186 adolescents aged 10 to 19 years old. Clinical variables were: body mass index, waist circumference, and neck, conicity index, systolic, diastolic and mean blood pressure; and metabolic variables were: triglycerides, glucose, total cholesterol, high-density lipoprotein and low-density lipoprotein cholesterol, insulin and Homeostasis Model Assessment index. It was considered statistically significant at p<0.05. Results:there was a prevalence of females, with 19.4% and 6.5% of overweight and obesity, respectively. The prevalence of insulin resistance was 42.5%. Distribution of clinical and metabolic variables of adolescents according to quartiles of the Homeostasis Model Assessment index blood pressure, blood glucose, and insulin increased the values of the Homeostasis Model Assessment index increased. Conclusion: insulin resistance is present in adolescents, and this condition is associated with the clinical and metabolic changes.